If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -16a = 12 Solving 10 + -16a = 12 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -16a = 12 + -10 Combine like terms: 10 + -10 = 0 0 + -16a = 12 + -10 -16a = 12 + -10 Combine like terms: 12 + -10 = 2 -16a = 2 Divide each side by '-16'. a = -0.125 Simplifying a = -0.125
| 3-2x=3x+8 | | 2x+7x=0 | | 18y-18=16y | | 3x+6=2y | | -6n=30 | | -6x-5=7 | | 104=13h | | 42=6m | | -1x-1=1x-21 | | 4p=32 | | 8q=56 | | -8p+3=-29 | | 7=-3c-2 | | 9x+3=7x-18 | | 6n+4=-26 | | 2x-9=-23 | | 6x+2=26 | | 3x-6=7x-8 | | 10x-2x=18 | | 6n+5n=4.5 | | 5x-14=4x-7 | | 6n+5ifn=4.5 | | 8-8y=3y-2 | | 6n+5withn=4.5 | | 3b+7=-2b-18 | | X-2(10+x)=12 | | 9x-8=6x+7 | | 7x-3=5x+7 | | 2+3(2-x)=14 | | 5(y-4)=7(2y+1) | | 10x-4=6(x+2) | | 3x+4+3x+4=29 |